Peramalan Persediaan Barang Menggunakan Metode Weighted Moving Average di CV. Multipaper Stationery - Merici, Angela; Saprudin, Usep (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
This research aims to implement the Weighted Moving Average method for forecasting inventory and getting prediction results on CV. Multipaper Stationery with the smallest possible error rate. In this method, researchers collect data from processes in the field to obtain the data needed in this research. The data taken is sales data for 2022-2023. Data analysis uses the Weighted Moving Average method. The results of the research show that from the six items used as research samples, the Weighted Moving Average value for the next 1 year is obtained, namely Sidu notebook 38 is 106764 pack, Sidu notebook 58 is 83877 pack, Techno Standard Pen is 40190 dozen, HVS Sinar Dunia A4 is 74589 rim, world rays F4 is 64137 rim and for Faber Castle pencil it is 40152 dozen.